Lacerated wound over posterolateral part of tongue: an unusual case report - Chandak, Suresh R.; Adgudwar, Shashank (International Surgery Journal, 2016)
Incised wound, cuts and lacerations over anterior 2/3rd of tongue is common but laceration over posterior part of tongue is not documented in literature. An adult female came with injury inside the oral cavity with active bleeding from laceration over posterior part of tongue which has been sutured primarily under local anesthesia.